Narrativas formativas: as memórias na constituição de uma professora-pesquisadora-participante - Morais, Denise Marques (2021)
The present work was developed through narratives, with the objective of narrating the experiences that formed me as a teacher-researcher-participant, in a process of professional transformation. These are narratives built from my voice, my memories and the theorists with whom I dialogued, seeking the production of meanings for the use of narratives as transformation strategies. The theoretical-methodological basis is based on the narrative research by Canadian authors Clandinin and Clonnelly (2015), who in the action of retelling stories bring contributions to the education, not only of ourselves but of others. Since historical transformations do not occur spontaneously, but are concrete and produced by men and women, we resort to an understanding that allows the researcher to reflect on their worldview and utopias. Narrative research addresses thinking and learning through storytelling, and retelling stories with the possibility of transforming that experience. In this work I present the composition and development of texts through the memories and observations about my teaching practice. The memory boxes with the creative narratives of stories were built with real characters, that were part of my constitution as a teacher-researcher-participant. In order to contextualize the historical times of memories, I resorted to the Brazilian educational historical context. All the work was based on Paulo Freire's theoretical framework, through the teaching knowledge that composed the meanings for my experiences as a teacher-researcher-participant in different educational contexts. Finally, I build a reflective letter based on the formative narratives, inviting my former teachers and my colleagues, to reflect with me about their being in the world.